Literature Survey on Harmony Search for feature selection - Chatterjee, P; Singh, D; Samaddar, A.B; Pal, B (International Journal of Computer Sciences and Engineering, 2025)
A new HS (Harmony Search) meta-heuristic algorithm has been conceptualized using the musical process of searching or a perfect state of harmony. Musical performances seek to find pleasing harmony (a perfect state) as determined by an aesthetic standard, just as the optimization process seeks to find a global solution (a perfect state) as determined by an objective function. The pitch of each musical instrument determines the aesthetic quality; just as the objective function value as determined by the set of values assigned to each decision variable. The new HS (Harmony Search) meta-heuristic algorithm has been derived based on natural musical performance processes that occur when a musician searches for a better state of harmony, such as during jazz improvisation. In this paper, the concept of harmony search algorithm has been used in feature selection and based on it; literature survey for the recent few years has been done.